PENGARUH HUBUNGAN INTERPERSONAL DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA GURU DI SMAN 1 KAMPAR DAN SMAN 2 KUOK - Silpa Wahyu Abadi; Susi Hendriani; Restu Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The research was conducted on SMA N 1Kampar and SMAN 2 Kuok in order to determine the influence of interpersonal relationships and work environment on job satisfaction of teachers. The samples in this study were as many as 105 teachers consisting of 75 teachers in SMA N 1 Kampar and 30 teachers at SMAN 2 Kuok. The analytical tool used was a questionnaire. Simultaneous regression (F test) showed that the independent variables studied (interpersonal relationships and work environment) jointly (simultaneously) have a significant effect on the dependent variable (job satisfaction). The magnitude of the effect that (R2) by the two independent variables is the same bersmaa-28.2% of the dependent variable, while the remaining 77.20% is influenced by other variables not examined in this study. Partial regression test (t test) showed that interpersonal relationships and work environment has a significant effect on the dependent variable (job satisfaction). Dominant variable affecting job satisfaction in SMA N 1 Kampar and SMAN 2 Kuok is the interpersonal relationship where tcounted value of the highest compared with the other independent variables.Keywords: Interpersonal Relations, Work Environment and Job Satisfaction